2013
DOI: 10.1159/000345977
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Hyperactivity of the Endolymphatic Sac

Abstract: Injury to the endolymphatic sac may play an important role in the pathogenesis of Ménière’s disease, an inner ear disorder characterized by hearing loss, tinnitus and attacks of vertigo. Isoimmunization of 16 inbred Lewis rats with a crude endolymphatic sac extract and complete Freund’s adjuvant induced hyperactivity of the endolymphatic sac. One group of rats was immunized by a single dose whereas a second group was immunized twice. Control animals were injected with Freund’s adjuvant in saline only. Serum wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…The protocol for use of ES extract for auto-immunization has previously been documented. In an immunization experiment similar to this study, the ES epithelial cell changes such as hyperactivity of the ribosome-rich cells and displacement of the mitochondria-rich cells were observed [6]. The changes were suggested to be the result of a chronic auto-inflammatory response in the epithelium of the ES.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The protocol for use of ES extract for auto-immunization has previously been documented. In an immunization experiment similar to this study, the ES epithelial cell changes such as hyperactivity of the ribosome-rich cells and displacement of the mitochondria-rich cells were observed [6]. The changes were suggested to be the result of a chronic auto-inflammatory response in the epithelium of the ES.…”
Section: Discussionsupporting
confidence: 75%
“…An explanation for the hearing loss in MD could be a compromised function of the ES and its capacity to participate in the endolymph homeostasis due to attacks of the ES, as suggested in the autoimmune saccitis model [6]. The autoimmune saccitis model suggested that attacks by auto-antigens, an inflammatory response, and recurrent focal inflammation of the ES epithelium could cause MD.…”
Section: Hearring Assessment Ii-after Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent case-control study (Kolla and Litwack 2000), the authors found a gene locus associated with bilateral MD suggesting that carriers may develop a NF-κB-mediated inflammatory response in MD. Friis et al (2013) found that the ES of rats that were isoimmunized with an ES extract developed specific tissue alterations identical to those present in the ES of active MD. Those findings support the theory that an immune injury may be important in the pathogenesis in MD.…”
Section: Can Surgery Initiate Es Secretion?mentioning
confidence: 87%
“…The localization of immunofluorescent labeling of the TLRs in the ES epithelium suggests that the receptors are located on the nonspecific (or immature) epithelial cells and/or the ribosome rich cells. Interestingly, the latter are implicated in the hyperreactivity seen in an experimental animal study of ES isoimmunization and the induction of autoimmune disease. In this perspective, it is also intriguing that the above‐mentioned cytokines, including variants of IL17, previously have been suggested to play a role in autoimmune diseases …”
Section: Discussionmentioning
confidence: 99%